The Effects of Product Type and Donation Magnitude on Willingness to Pay More for a Charity‐Linked Brand - Strahilevitz, Michal (Journal of Consumer Psychology, 1999)
This research investigates how the nature of a product and the magnitude of a donation to charity interact to determine the effectiveness that a charity incentive will have in promoting a product. The results suggest that sensitivity to magnitude in the case of charity incentives (i.e., the size of the contribution made per purchase) is not as strong as sensitivity to magnitude in the case of monetary incentives (i.e., the percentage of the price being discounted). In addition, it is found that with large donation magnitudes competing with large monetary incentives, charity incentives will be significantly more effective in promoting products perceived as “frivolous luxuries” (e.g., a hot fudge sundae or a luxury cruise) than in promoting products perceived as “practical necessities” (e.g., a roll of paper towels or a new washing machine). In contrast, in the case of small donation magnitudes competing with correspondingly small monetary incentives, no significant difference in charity incentive effectiveness is observed between different product types. Finally, the effects of donation magnitude and product type are examined in the context of choosing among multiple charity‐linked brands. It is found that whereas brands linked to large donations are more likely to be preferred with frivolous products, brands linked to smaller donations are more likely to be favored with practical products.